IMPLEMENTASI TEORI SIBERNETIK PADA PEMBELAJARAN PAK DI TINGKAT SMP - Dion Stefanus Adu; Yedija A. M. Tahun; Yandri E. Fina; Jesi M. Ottu; Reiner Sabat; Maria Indriani Sesfao (ADIBA : JOURNAL OF EDUCATION, 2025)
This study explores the implementation of Cybernetic Theory in the learning process of Christian Religious Education (CRE) at the junior high school level. Cybernetic Theory emphasizes the role of feedback, control systems, and dynamic interaction between teacher, student, and learning environment. In this context, the teacher acts as a regulator who directs the flow of information and guides students through a process of continuous learning adjustment. This research highlights how feedback mechanisms such as reflection, evaluation, and teacher-student dialogue can improve student engagement and understanding in CRE classes. The study also examines the integration of technology as a medium for interactive learning, which aligns with cybernetic principles. Through qualitative analysis of observations and interviews, the findings indicate that the application of Cybernetic Theory encourages more responsive, participatory, and student-centered learning in CRE. This approach not only enhances cognitive and spiritual growth, but also cultivates ethical awareness and self-regulation among students. The study concludes that Cybernetic Theory offers a relevant and adaptive pedagogical framework for Christian education in the digital era, especially in addressing the developmental needs of adolescents in junior high schools.